Strategic Spatial Planning in Irish Local Communities - BURCEA Ștefan Gabriel; REID Catriona (Applied Research in Administrative Sciences)
This article provides a comprehensive overview of the planning system in Ireland with specific respect to the Planning Acts, the production of development plans, and the different types of planning application including Strategic Infrastructure Developments. Following this, the case of the Rioja Estates retail outlet centre in Carrigtwohill, County Cork, will be examined in light of contemporary issues in Irish planning. The study aims to identify and analyze the particularities regarding strategic planning at the local level, in particular, the way in which the spatial planning process was managed in Irish local communities. The research methodology considered is the case study based on the document analysis (administrative documents and strategic documents of local authorities of Cork County and public statements of officials in the local press) in the context of which the opportunity to build a retail outlet centre in Carrindtwohill was analyzed. Specific attention will be paid throughout the article to the role of the relatively new Office of the Planning Regulator, which was established in 2019 to oversee the correct implementation of planning policy by local authorities, and which played a pivotal role in the Rioja Estates case.